Exchange rate as an unconventional tool of monetary expansion on the example of The Czech Republic - Purnochová, Barbora (2015)
Recent crisis and economic recession caused in many countries problems with drop in inflation and overall downturn in economic growth. The Central Banks found themselves in so called zero lower bound. This thesis describes the situation of deflation, zero lower bound and liquidity trap. These conditions called for the use of alternative monetary policy tools. The main goal of the thesis is to evaluate the use of foreign exchange rate intervention as unconventional tool in a small open economy with inflation targeting regime represented by the Czech Republic in the analytic part. Thesis examines other non-standard instruments and provides reasons for the Czech National Bank decision. The analysis shows the complexity of the issue and provides the evidence that exchange rate commitment was not displayed to the desired price level. The tool could lead to expected repercussion, but the effect is impacted by factors, which Central Bank cannot control. The effect of the CB way to fight the decreasing inflation will be better shown after the CB exit from the commitment.